2006
DOI: 10.1016/j.apnr.2005.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Testing of the Individual Nutrition Rx assessment process among nursing home residents

Abstract: The purpose of this article is to describe the Individual Nutrition Rx (INRx) assessment process and report preliminary findings on baseline nutritional status, common nutrition problems and specific individualized interventions. The INRx utilizes a predictive model for participant identification, a systematic assessment process, and evidence-based interventions to improve nutritional status of atrisk residents. Nineteen percent of participants had abnormal serum albumin levels and 32.8% had abnormal serum pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 7 publications
1
9
1
Order By: Relevance
“…Among that group, 17 (81.0%) were on NG feeding. Our results were similar to those of Crogan and Alvine (2006), who surveyed 80 nursing home residents and found that 19% had albumin levels < 3.5 g/dl. Liau (2003) studied 111 residents in Taiwan with NG feedings in a long-term care facility and found that 71 residents (76.3%) had protein deficiency.…”
Section: Discussionsupporting
confidence: 93%
“…Among that group, 17 (81.0%) were on NG feeding. Our results were similar to those of Crogan and Alvine (2006), who surveyed 80 nursing home residents and found that 19% had albumin levels < 3.5 g/dl. Liau (2003) studied 111 residents in Taiwan with NG feedings in a long-term care facility and found that 71 residents (76.3%) had protein deficiency.…”
Section: Discussionsupporting
confidence: 93%
“…No RCTs or adequately powered, good quality studies were identified that addressed patient-specific issues that might impact on dietary intake. In other studies, a number of factors were identified that impacted upon nutritional status in nursing homes, including poor appetite, poor positioning (Crogan & Alvine, 2006), poor oral health, swallowing difficulties (Kayser-Jones, 1996, 1997, level of alertness (Westergren et al, 2001) and degree of assistance required (Thomas et al, 1991). Only one study was identified that attempted to address these issues in a patient-specific approach (Christensson et al, 2001).…”
Section: Patient-specificmentioning
confidence: 99%
“…This process of care goes beyond the basic required nutritional assessment by (1) increasing the number of criteria used by nurses for assessment; (2) increasing the array of interventions available to nursing staff; (3) providing staff education to implement interventions; (4) systematizing the evaluation of responses; and (5) systemically establishing a feedback loop between evaluation and planning of care. The goal of the INRx process of care is to develop a more complete and accurate comprehensive assessment of resident needs that leads to improved nutritional status, enhanced quality of life, decreased morbidity and lower healthcare utilization (Crogan and Alvine, 2006).…”
Section: Individual Nutrition Rx Process Of Carementioning
confidence: 99%
“…Of these seven problems, three were predictive of resident outcomes. Interventions targeting these problems could positively affect nutrition status and prevent malnutrition (Crogan and Alvine, 2006;Crogan et al, 2007). The purpose of this article is to describe those three nutritional problems, discuss their predictive value and encourage attention to these problems to avoid their potential adverse outcomes in nursing homes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation